PERANCANGAN DAN PEMBUATAN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA PENGAJARAN TEKNIK ELEKTRONIKA - Iim Abdul Rohim; Putra Jaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to produce learning media for electronic components using Augmented Reality technology by knowing the performance and magnitude of the feasibility value of learning media for electronic components using the Augmented Reality technology. Designing and making applications using the steps of the waterfall method include: 1) Designing, 2) Architectural Design and Interfaces, 3) Encoding / Programming, and 4) Testing. Application programs are made with laptops that have Intel®core ™ i3 CPU@2.00GHz processor specifications, 4.00GB RAM, Intel® HD Graphics520, 1TB hard drive, with a Windows 10 Pro 64-bit X64 operating system. Integrated Development Environment (IDE) in making this application is Unity 2018.3.6f1 with the marked based tracking method. Based on the results of the feasibility test conducted by two material experts as well as two media experts, that in the aspect of application material got an average value of a total score of 63 out of 68. In the media aspect the application got an average score of 84.5 from the total score of 96 Both of these scores give interpretation that the application of Augmented Reality learning media in teaching electronic engineering is very feasible to be used as a learning media.Keywords: Augmented Reality, Learning Media, Electronic Engineering, Unity 3D